2001
DOI: 10.1054/bjoc.2001.2012
|View full text |Cite
|
Sign up to set email alerts
|

The relation between mortality from malignant melanoma and early detection in the Cancer Research Campaign Mole Watcher Study

Abstract: Summary Between 1987 and 1989 the Cancer Research Campaign funded a health education programme for the early detection of cutaneous malignant melanoma in the general population in 6 health districts of England and 1 health board in Scotland (population of 3 million). The intervention was evaluated by studying its effects on annual and cumulative mortality rates for melanoma. Population-based data on mortality from melanoma were collected in the intervention areas, the health regions covering those areas, and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…These campaigns were regularly followed by an increase in melanoma incidence, associated in most cases with an increase in the proportion of thin melanomas. However, they generally failed to show a decrease in either melanoma‐related mortality and/or in incidence of thick melanomas . A recent American study concluded that surveillance and early detection efforts in the U.S.A. have not resulted in a substantial reduction of tumours with prognostically unfavourable thickness .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These campaigns were regularly followed by an increase in melanoma incidence, associated in most cases with an increase in the proportion of thin melanomas. However, they generally failed to show a decrease in either melanoma‐related mortality and/or in incidence of thick melanomas . A recent American study concluded that surveillance and early detection efforts in the U.S.A. have not resulted in a substantial reduction of tumours with prognostically unfavourable thickness .…”
Section: Discussionmentioning
confidence: 99%
“…However, they generally failed to show a decrease in either melanoma-related mortality and/or in incidence of thick melanomas. [23][24][25][26][27][28][29] A recent American study concluded that surveillance and early detection efforts in the U.S.A. have not resulted in a substantial reduction of tumours with prognostically unfavourable thickness. 30 In this context, our results, although limited to a small geographical area, seem original and of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly individuals should be the focus of health promotion activities [1, 2], although the approach to early detection does not always result in a significant reduction in melanoma mortality [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Early detection of melanoma can benefit from education of the general population to become aware of the early signs, targeted interventions on high-risk groups and individuals [19]. Targeted interventions can focus on very high-risk groups such as those with a family history of the disease or those with a phenotype, which carries a higher risk than the average population, such as those with fair skin or a large number of naevi.…”
Section: Melanomamentioning
confidence: 99%